Towards Competitive Livestock, Poultry, and Dairy Industries: Consolidated Benchmarking Study - Roehlano M. Briones; Isabel B. Espineli (Philippine Institute for Development Studies (PIDS), 2022)
This benchmarking study is undertaken to compare domestic performance of LPD industries in the Philippines, with other large LPD producers and consumers in Asia, namely China, Thailand, and Vietnam, supplemented with figures from major global players. In the case of swine, in the Philippines, unit cost of production of commercial farms is lower than in backyard farms owing to economies of scale. Cost per unit in commercial farms in the Philippines is among the highest of the countries studied, mostly due to higher cost of feed and grower stock. As with swine, economies of scale allow commercial broilers to reduce cost per kg of broiler. Cost per unit for commercial scale broiler farms is among the lowest in Philippines compared with China, Thailand, and Vietnam. High tariffs on corn imports is driving up the cost of livestock and poultry feed. Finally, Dairy cattle and buffalo milk at semi-commercial scale can be profitable, though the business case for backyard dairy needs to be strengthened. The Philippines has implemented a set of regulatory and support policies for the LPD industries, covering regulations, support programs, trade policies, Policy recommendations of the study are as follows: 1) Undertake a comprehensive review of trade policies affecting the value chain towards greater competitiveness of the LPD industries; 2) Earmark the collections from tariffs on pork and chicken imports to fund regulatory services and production support; 3) Invest in research and data collection as inputs to policy and program development; 4) improved delivery of technical assistance, regulatory services, and production support. 5) Reset the oversight system over the LPD industries in terms of regulatory compliance, zoning, imposition of grades and standards, food safety and animal welfare; 6) Focus on upgrading technology and business practices for backyard operators using a collaborative approach to extension. 7) Strengthen FOs to encompass most or all backyard operators to facilitate delivery of government assistance, technical and regulatory services, and realize gains from economies of scale and scope.
Keywords: 330; agricultural benchmarking; value chain; competitiveness